1998
DOI: 10.1159/000028639
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Fibrous Dysplasia and Aneurysmal Bone Cyst of the Skull Base

Abstract: The combination of fibrous dysplasia and aneurysmal bone cyst of the skull base is extremely rare yet it should be recognized, lest the rapid growth of the lesion and the radiological picture lead to the wrong diagnosis of a malignant process. We report on a 6½-year-old patient who suffered from concomitant fibrous dysplasia and aneurysmal bone cyst of the skull base. He is still disease-free 4 years postoperatively. The treatment of choice remains early surgical removal of the maximal amount of involved bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
0
22
0
9
Order By: Relevance
“…4,8 A report of an orbital and palpebral arteriovenous malformation was described in a patient with MAS; 32 however, vascular anomalies are not associated features of MAS. There are several reports of aneurysmal bone cysts forming in the setting of fibrous dysplasia; 10,21 however, the imaging and angiographic appearance in this case was not that of an aneurysmal bone cyst. GPS is a rare inherited bleeding disorder characterized by thrombocytopenia and an absence of platelet agranules, resulting in typical gray platelets on peripheral smears.…”
Section: Postoperative Coursementioning
confidence: 59%
“…4,8 A report of an orbital and palpebral arteriovenous malformation was described in a patient with MAS; 32 however, vascular anomalies are not associated features of MAS. There are several reports of aneurysmal bone cysts forming in the setting of fibrous dysplasia; 10,21 however, the imaging and angiographic appearance in this case was not that of an aneurysmal bone cyst. GPS is a rare inherited bleeding disorder characterized by thrombocytopenia and an absence of platelet agranules, resulting in typical gray platelets on peripheral smears.…”
Section: Postoperative Coursementioning
confidence: 59%
“…The cystic degeneration of an FD causing rapid enlargement of FD lesions was documented by ClausHermberg et al occurring in a 15-year old patient in 2011 [19]. In a literature review, Haddad et al reported 6 cases of concomitant FDs and ABCs of the skull, and described their association as ''exceedingly rare'' [18]. No reports were found of FDs arising from ABCs.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the unclear relationship between these two entities, the literature describes the development of an ABC (or a malignant lesion outbreak) from a previous FD, or the coexistence of both conditions at the same time [15][16][17][18]. The cystic degeneration of an FD causing rapid enlargement of FD lesions was documented by ClausHermberg et al occurring in a 15-year old patient in 2011 [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, large studies that may have included some pediatric patients had not published their detailed results based on age groups, [5][6][7] and the current literature is mainly limited to published case reports. [9][10][11][12][13][14] There are only 2 case reports describing the presence of fluid-fluid level in LCH. 12,14 In both of these cases, the FFL was demonstrated on both CT and MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma, benign lesions of the skeleton (eg, chondroblastoma, chondromyxoid fibroma, osteoblastoma, giant cell tumor, fibrous dysplasia), and even some malignant tumors (eg, osteosarcoma, chondrosarcoma, hemangioendothelioma) have been associated with development of aneurysmal bone cysts. 10,17,23 In the setting of fibrous dysplasia, secondary ABC formation can occur in addition to the more common evolving fibrous dysplasia with lytic areas or cystic degeneration. 24 Cephalohematoma is a subperiosteal hemorrhage that results from tearing of delicate vessels that traverse through the bone into the scalp.…”
Section: Discussionmentioning
confidence: 99%